Effects of storage time and tree height on sugar and starch compositions of oil palm trunk biomass - Yahya, Mohd Khairul Azri (2012)
Effects of storage time and height of trees on sugar and starch compositions of the oil palm biomass at age 25 years of three logs were studied. Each log was divided into 4 different height portions, which were top part (TOP), middle of top part (MDT), middle of bottom part (MDB) and bottom part (BOT). The samples were stored for 120 day and within this period, the samples were cut into the disc on 0, 1st, 3rd, 7th, 15th, 30th, 60th, 90th and 120th day. Each disc was divided into 3 cross-sectional segments, which were inner part (A), middle part (B) and outer part (C). Then, these discs were squeezed with machine press to obtain the sap of the oil palm trunk. Gas Chromatographic (GC) analysis showed the increasing glucose content in the sap with the increasing storage time. The HPLC analysis indicated the presence of glucose, fructose, galactose, sucrose and inositol in OPT sap.The Starch content by Humprey and Kelly method showed decreasing amount with the prolonged storage time. Higher starch content was the upper portions of the OPT compared to the bottom part of the trees. This coincides with the distribution of starch granules observed from Scanning Electron Microscopy (SEM) analysis of the trunk.